2007
DOI: 10.1002/bdd.563
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic hepatic failure on disposition kinetics of valproate excretion through a phase II reaction in rats treated with carbon tetrachloride

Abstract: Abstract:We examined the influence of chronic hepatic failure on the disposition kinetics of valproate (VPA) excretion via a phase II reaction in rats treated with carbon tetrachloride (1.0 mg/kg, s.c., 3 times a week) for 2 or 3 months. There was no significant difference in the plasma concentration-time courses of VPA among control and two treated groups up to 120 min after i.v. administration of VPA (75 mg/kg), but subsequently the plasma concentrations of the treated groups declined significantly below the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…In some cases, the drug metabolizing enzymes may be induced by the presence of liver disease (Aweeka et al, 1999;Lu & Cederbaum, 2008), whereas Igarza et al (2006Igarza et al ( , 2004Igarza et al ( , 2002, Bengtsson et al (1997) and Girard and Matte (1995) Rule et al (1996) and Nouws et al (1983) in other cases, they can be inhibited (Orlando et al, 2006). In addition to these more obvious effects of liver disease, hepatic dysfunction can also lead to changes in plasma protein binding (e.g., Klammt et al, 2008), intestinal absorption (Takaya et al, 1989;Khemawoot et al, 2007), and decreased renal perfusion and glomerular filtration (Gundling et al, 2008).…”
Section: Hepatic Impairmentmentioning
confidence: 99%
“…In some cases, the drug metabolizing enzymes may be induced by the presence of liver disease (Aweeka et al, 1999;Lu & Cederbaum, 2008), whereas Igarza et al (2006Igarza et al ( , 2004Igarza et al ( , 2002, Bengtsson et al (1997) and Girard and Matte (1995) Rule et al (1996) and Nouws et al (1983) in other cases, they can be inhibited (Orlando et al, 2006). In addition to these more obvious effects of liver disease, hepatic dysfunction can also lead to changes in plasma protein binding (e.g., Klammt et al, 2008), intestinal absorption (Takaya et al, 1989;Khemawoot et al, 2007), and decreased renal perfusion and glomerular filtration (Gundling et al, 2008).…”
Section: Hepatic Impairmentmentioning
confidence: 99%
“…In male SD rats, exposure to carbon tetrachloride (640 mg/kg per 2 days for 45 days) in a long-term treatment decreases hepatic Mrp2 mRNA expression (Okumura et al, 2007). In rats with chronic hepatic failure induced by carbon tetrachloride (1.0 mg/kg, subcutaneously; s.c., 3 times per week) for 2 or 3 months, Mrp2 mRNA expression was significantly lower than in the control group (Khemawoot et al, 2007). …”
Section: Regulation Of Hepatic Abcc2/mrp2 Transporters By Xenobioticsmentioning
confidence: 67%
“…Khemawoot et al . reported that the enzyme activity of UDP‐glucuronosyltransferase in the liver of rats treated with CCl 4 decreased significantly 11. In addition, the cytosolic glutathione S‐transferase activities were markedly decreased following the development of CCl 4 ‐alcohol‐induced liver fibrosis 12.…”
Section: Resultsmentioning
confidence: 99%